„Aleksander I jako król polski” pędzla Niccoli Montiego (1819) – malarstwo portretowe w służbie propagandy Królestwa Kongresowego - Mikołaj Getka-Kenig (Quart)
The Emperor of Russia Alexander I as a Polish King by Niccola Monti, dated 1819, from the collection of the National Museum in Warsaw (previously held in the Royal Castle collection in Warsaw), serves as an exceptional example of an elaborate iconographic programme among “Polish” depictions of the founder of the Kingdom of Poland (Congress Poland). The painting unevenly emphasises the three strands of the official cult of Alexander I as the “resurrector” of Poland after the Congress of Vienna. First and foremost, it stresses justice, followed by a Polish-Russian union and, finally, universal peace guaranteed forever. These elements form together a coherent message: national “resurrection” is an act of justice by Alexander I, while remaining contingent upon a union with Russia and the permanence of the international order established at the Congress of Vienna. Justice was given particular prominence – through its personified statue dominating this composition – because of the function of this painting, intended for a court house (more precisely, the Court of Appeal in Warsaw). Alexander’s justice towards the Poles, as the architect of Congress Poland, could therefore also pertain to the justice administered by the courts, which issued their rulings in the name of the fair “resurrector”. In terms of its content, the painting is a product of the political discourse of the time, representing the authorities’ stance on the Kingdom’s status as a “resurrected” Polish state. In terms of form, on the other hand, its originality within the scope of an elaborate iconographic programme presumably stems from the individual preferences of the client, namely the president of the Court of Appeal. He was a devoted Freemason, which may explain his inclination towards such allegorical depictions.